Analisis Kesulitan Mahasiswa dalam Pembelajaran BIPA di Balai Bahasa Universitas Pendidikan Indonesia - Rihhad Nazhmi Maulana; Salma Aulia Rahmadzikra; Zahra Nabila Yusuf; Mia Nurmala (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
The Indonesian Language for Foreign Speakers (BIPA) program is gaining global interest, yet its learning process still faces various challenges. This study aims to identify and analyze difficulties experienced by international students in learning Indonesian at the Language Center of Universitas Pendidikan Indonesia. A descriptive qualitative method was employed, utilizing in-depth interviews with two foreign students. The findings reveal that the main challenges include vocabulary acquisition, differences in grammatical structure, accent adaptation, as well as adjusting to Indonesian culture and native speakers’ speaking speed. Proposed solutions involve repeated practice, direct interaction with native speakers, and the use of interactive learning methods. In conclusion, a deeper understanding of these challenges can help design more effective and adaptive BIPA learning strategies.